IMPLEMENTATION OF TEAM BASED PROJECT LEARNINGMETHOD AT D’TECH ENGINEERING SALATIGA - Nur Eka Anggraini; Abdul Malik; Imam Shofwan (European Journal of Humanities and Educational Advancements, 2023)
In order to achieve success and competitiveness in the global society, learners must possess skills as effective communicators, creators, critical thinkers, and collaborators. Critical thinking, technological literacy, and problem-solving skills are considered essential competencies for learners in the 21st century. Team Project-Based Learning (PjBL) is regardedas an innovative collaborative learning method that has a direct impact on learners. D’tech Engineering serves as a place where many young individuals collaborate to create technological innovations in the field of manufacturing. This study aims to 1) understand the implementation of the Team Project-Based Learning model at D’tech Engineering in Salatiga and 2) examine the outcomes of implementing the Team Project-Based Learning model at D’tech Engineering in Salatiga. This research employs a qualitative approach, with the subjects being the employees working there and the informants being the CEO of D’tech Engineering in Salatiga. Data is collected through observation, interviews, and documentation. Data validity is ensured through source and method triangulation, and data analysis is carried out through data reduction, data presentation, and drawing conclusions. The findings of this research are as follows: 1) The learning steps align with the syntax developed by The George Lucas Educational Foundation, which includes essential questions, designing products, scheduling project completion, monitoring project activity and development, testing results, and evaluation. 2) The outcomes of implementing this learning approach indicate that employees are able to collaborate and solve problems in project development, enhance creativity, and become more independent while actively participating in the workforce.